Design and Analysis of Ultrafast Pulsed Laser Systems for Precision Micromachining in Electronic Materials (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The increasing demand for miniaturization and high-precision fabrication in electronic materials, including semiconductors, MEMS, and microelectronics packaging, necessitates advanced micromachining techniques capable of producing microscale features with minimal thermal damage. This study presents the design and analysis of ultrafast pulsed laser systems tailored for precision micromachining applications in such materials. Theoretical modeling encompassed ablation threshold calculations, thermal diffusion analysis, and spot size-fluence optimization, revealing that femtosecond pulses (\~300 fs) enable cold ablation with negligible heat-affected zones due to their ultrashort energy deposition timescales.An experimental setup was developed using a femtosecond laser (1030 nm, 300 fs) integrated with galvanometric scanners and precision stages, processing silicon wafers, glass substrates, and thin metal films. Machining parameters, including pulse energy (5–150 µJ), repetition rate (100–500 kHz), and scanning speed (0.1–10 mm/s), were systematically varied. Results demonstrated high-quality micromachining outcomes, achieving minimum feature sizes of \~1.5 µm, smooth surfaces with RMS roughness of 20–50 nm, and minimal redeposition or tapering. Pulse characterization via autocorrelation and FROG confirmed clean temporal profiles, while system stability tests showed